EFFECT OF PRODUCT QUALITY, PROMOTION, AND BRAND IMAGE BRAND TRUSTON THE PURCHASE DECISION TOYOTA AVANZA IN CITY COMMUNITIES - Muhammad Furqan; Mariyudi; T.Edyansyah; Heriyana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the effect of product quality, promotion, Brand Image and Brand Trust on purchasing decisions for Toyota cars (a case study of the Toyota Avanza in Lhokseumawe City Communities). The research method in preparing this thesis uses quantitative research methods. The sampling method uses a non-probability sampling method, because the population studied is infinite (a population whose number and identity of population members is unknown). The results of the conclusion obtained that. The product quality variable concludes that Ho1 is rejected and Ha1 is accepted, so it is in accordance with the decision that the variable X1 has no effect on the Toyota Avanza Car Purchase Decision for the Community in Lhokseumawe City, while for the promotion variable, Brand Image and Brand Trust partially affect purchase decisions.